A Novel Mangled Upper Extremity Injury Assessment Score. Issue 9 (September 2019) - Savetsky, Ira L.; Aschen, Seth Z.; Salibian, Ara A.; Howard, Katherine; Lee, Z-Hye; Frangos, Spiros G.; Thanik, Vishal D.
Abstract : Background: Managing mangled upper extremity injuries is a challenging problem because multiple tissue components including soft tissue, muscle, tendon, bone, nerves, and vessels are involved. The complexity of these injuries has hindered the development of accurate scoring systems and treatment algorithms. Methods: Patients with mangled upper extremities presenting to a metropolitan level 1 trauma center in New York City over a 10-year period were identified. A mangled upper extremity was defined as any injury to ≥3 tissue components involving the extremity proximal to the digit. Results: The injuries and outcomes of 76 patients were evaluated and used to create a Mangled Upper Extremity Score (MUES). One point was assigned for each of the following injury characteristics: patient age >40, fasciotomy needed, bony fixation required, bony defect present, revascularization required, crush injury mechanism, degloving or avulsion injury present, and a soft tissue defect >50 cm 2 . The MUES correlated with the number of complications ( P value = 1.96 × 10 −7 ) and length of hospital stay ( P value = 3.95 × 10 −7 ). Next, a Mangled Extremity Severity Score (MESS) equivalent was calculated for each patient. There was no correlation between the MESS and the number of complications ( P value = 0.92) or length of hospital stay ( P value = 0.35). Conclusions: Existing extremity scoring systems, including the MESS, are not reliable in predicting the success of limb salvage attempts or outcomes of mangled upper extremity injuries. The MUES developed in this study correlates significantly with important outcome measures including the number of hospital complications and length of hospital stay.